2022
DOI: 10.1177/13694332211022070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of pre-stressed concrete transmission poles under synoptic wind loading

Abstract: A numerical model capable of predicting the dynamic response of pre-stressed concrete transmission poles under both the mean and fluctuating components of synoptic wind loads is developed in this study. A full non-linear dynamic analysis is conducted under a time history variation of wind velocity. The peak total responses, such as conductors’ reactions and poles’ base moments, are determined from this analysis. The same analysis is repeated in a quasi-static manner. Dynamic amplification factors (DAF), define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Zeynalian [1] conducted Abaqus simulation and bending experiments on square concrete poles in the distribution network, respectively, and concluded that the normal bearing environment would not cause damage to the poles in the standard installation state. Ibrahim et al [19] established a numerical model of the dynamic response of the prestressed concrete pole and found that the resonance effect of the wire is dominant at low wind speed. Gao et al [20] tested the ultimate bearing capacity of ultra-high strength concrete electric pole, established a finite element model with Abaqus software, and obtained the ultimate bearing capacity of ultrahigh strength concrete electric pole through experiments and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Zeynalian [1] conducted Abaqus simulation and bending experiments on square concrete poles in the distribution network, respectively, and concluded that the normal bearing environment would not cause damage to the poles in the standard installation state. Ibrahim et al [19] established a numerical model of the dynamic response of the prestressed concrete pole and found that the resonance effect of the wire is dominant at low wind speed. Gao et al [20] tested the ultimate bearing capacity of ultra-high strength concrete electric pole, established a finite element model with Abaqus software, and obtained the ultimate bearing capacity of ultrahigh strength concrete electric pole through experiments and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%